The humble story of Don Quixote: reflections on the birth of the modern novel - Bandera, Cesáreo (Catholic University of America Press, 2010)
A story "naked and unadorned" -- The picaresque point of reference 1 : Guzmán de Alfarache -- The picaresque point of reference 2 : the Buscón -- Don Quixote's madness and modernity -- De te fabula narratur -- Unamuno's enthusiastic Quijotismo and the envy of Cain -- From Don Quixote's penitence to the episode of the lion -- Unamuno's story of Cain and Abel and the Curioso impertinente -- The pastoral precedent -- The desire of the obstacle -- Juan Palomeque's Inn -- Tricksters tricked.